2005
DOI: 10.1038/nature03486
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sleep in Drosophila Shaker mutants

Abstract: Most of us sleep 7-8 h per night, and if we are deprived of sleep our performance suffers greatly; however, a few do well with just 3-4 h of sleep-a trait that seems to run in families. Determining which genes underlie this phenotype could shed light on the mechanisms and functions of sleep. To do so, we performed mutagenesis in Drosophila melanogaster, because flies also sleep for many hours and, when sleep deprived, show sleep rebound and performance impairments. By screening 9,000 mutant lines, we found min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
447
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(466 citation statements)
references
References 45 publications
15
447
0
4
Order By: Relevance
“…Because the durations in daily firing patterns in SCN neurons deficient for Kv1.4 were not significantly different from WT SCN neurons, the behavioral phenotype may result from the functioning of Kv1.4-encoded I A channels outside the SCN. Together with previous studies linking Kv channel functioning to sleep in mice and in flies (Vyazovskiy et al, 2002;Cirelli et al, 2005;Douglas et al, 2007;Espinosa et al, 2008;Koh et al, 2008), the results here support the interesting possibility that modulation of Kv channels (and other conductances that regulate intrinsic neuronal excitability) play critical roles in both circadian biology and sleep.…”
Section: Circadian Locomotor Activity Is Altered In Kv14supporting
confidence: 86%
“…Because the durations in daily firing patterns in SCN neurons deficient for Kv1.4 were not significantly different from WT SCN neurons, the behavioral phenotype may result from the functioning of Kv1.4-encoded I A channels outside the SCN. Together with previous studies linking Kv channel functioning to sleep in mice and in flies (Vyazovskiy et al, 2002;Cirelli et al, 2005;Douglas et al, 2007;Espinosa et al, 2008;Koh et al, 2008), the results here support the interesting possibility that modulation of Kv channels (and other conductances that regulate intrinsic neuronal excitability) play critical roles in both circadian biology and sleep.…”
Section: Circadian Locomotor Activity Is Altered In Kv14supporting
confidence: 86%
“…The apparent loss of rhythms may be caused by the overall increased rate of divisions. The other mutants tested here do not have sleep phenotypes as extreme as the reduction of sleep in sss mutants (23)(24)(25)(26), which may account for the maintenance of normal stem cell activity in these flies. However, it is possible that some sleep-regulating pathways also regulate stem cell activity, whereas others do not.…”
Section: Sleep-promoting Factor Sss Affects Mitotic Activity Of Male mentioning
confidence: 80%
“…altered (Fig. 3A), presumably because of their less severe sleep phenotypes (23)(24)(25)(26). Alternatively, SSS may modulate stem cell divisions through mechanisms unrelated to its function in sleep, or the sleep-regulating pathways affected in sss flies may be different from the pathways altered in other sleep mutants (discussed below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genetic studies have begun to identify mutations in humans, mice, and flies that alter sleep time and sleep homeostasis (27)(28)(29)(30). Similarly, ethological studies have reported instances where animals can sustain waking for extended periods of time without exhibiting a homeostatic response [e.g., cetacean (31) and white-crown sparrow (32)].…”
Section: Discussionmentioning
confidence: 99%